Strategic talent management: the impact of employer branding on the affective commitment of employees - Alves, P. (2021)
In a globalization context, underlined by the speed of technological transformation and increasingly competitive markets, the perspective of human capital, as an asset of strategic importance, stands out in differentiating human resource practices. Under this reality, the employer branding (EB) concept gains more and more importance as a strategic tool to attract, retain, and involve human capital, given that this has become a source of competitive advantage to companies. Within this context, this study aimed to evaluate the relationship between employer branding strategies implemented by organizations, as well as their impact on the employee’s affective commitment, evident in certain organizational cultures, which are sustained over time. The methodological framework applied to this study is quantitative, and the data collection was carried out with the application of an employer branding and an affective commitment questionnaire. To achieve a good representation of the active population, the sample of the quantitative study was composed of 172 individuals, working in the public and private sectors in Portugal, exercising different positions in the different sectors of activity. Results obtained with these techniques indicate a high level of affective organizational commitment (AOC) of employees in the organizations surveyed, suggesting that affective commitment develops when the individual becomes involved and identifies with the organization.